ANOMALIES OF VARIATIONAL PHASE-SHIFTS - Adhikari, S. K. (Elsevier B.V., 1991)
It is demonstrated, contrary to various claims, that the phase shifts calculated via variational principles involving the Green function may exhibit anomalous behavior. These anomalies may appear in variational principles for the K matrix (Schwinger variational principle) of potential V, for (K-V) (Kohn-type and Newton variational principles), and other variational principles of higher order (Takatsuka-McKoy variational principle).